2022
DOI: 10.1007/s11130-022-00995-y
|View full text |Cite
|
Sign up to set email alerts
|

Spray-drying Microencapsulation of an Extract from Tilia tomentosa Moench Flowers: Physicochemical Characterization and in Vitro Intestinal Activity

Abstract: Silver linden (Tilia tomentosa Moench, TtM) flowers possess several health-promoting properties, especially at the neurological level, such as intestinal relaxation activity associated with specific flavonols, particularly quercetin and kaempferol derivatives. However, such molecules are susceptible to degradation upon different triggers like heat, light and extreme pH values. To overcome the scarce stability of TtM flowers bioactive molecules and make them suitable for developing functional food and supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This finding is significant from a pharmaceutical-technological perspective since the microencapsulated extract is preferable to traditional, commonly used tinctures, particularly in terms of protecting the stability of active compounds [ 18 ]. In line with our findings, Mainente et al (2022) reported that the microencapsulated extract of Tilia tomentosa flowers exhibited slightly weaker in vitro inhibitory activity on ileal motor functions compared to the non-encapsulated form, although the difference was comparable [ 25 ]. The rationale for microencapsulation is based on the maintenance of extract bioactivities, along with providing additional positive quality parameters for the final products.…”
Section: Resultssupporting
confidence: 92%
“…This finding is significant from a pharmaceutical-technological perspective since the microencapsulated extract is preferable to traditional, commonly used tinctures, particularly in terms of protecting the stability of active compounds [ 18 ]. In line with our findings, Mainente et al (2022) reported that the microencapsulated extract of Tilia tomentosa flowers exhibited slightly weaker in vitro inhibitory activity on ileal motor functions compared to the non-encapsulated form, although the difference was comparable [ 25 ]. The rationale for microencapsulation is based on the maintenance of extract bioactivities, along with providing additional positive quality parameters for the final products.…”
Section: Resultssupporting
confidence: 92%
“…A complex interplay of different factors, including the degree of glycosylation and/or acylation, appears to affect the affinity of each ACN to the polymers of the coacervates and, in turn, the overall encapsulation efficiency and stability of the molecules. Indeed, as we recently described for silver linden ( Tilia tomentosa ) flavonoids, the stability of encapsulated molecules is positively influenced by the interaction with the matrix [ 44 ]. To the best of our knowledge, this is the first time that the loading of a coacervate with a complex phenolic mixture is characterised at the single-molecule level.…”
Section: Resultsmentioning
confidence: 99%
“…Among different drying techniques, spray drying is one of the most widely used processes for liquid food products at a commercial scale which also allows the scope for encapsulating beneficial microorganisms such as probiotics. 15 Nonetheless, the high drying temperatures in spray drying decreases probiotic viability and also causes a glassy state in the developed powder. Spray drying is also limited to liquid food products, thereby restricting the use of this technique for a variety of food products.…”
Section: Introductionmentioning
confidence: 99%